Unpacking the Schengen Visa Regime. A Study on Bureaucrats and Discretion in an Italian Consulate. Issue 2 (2nd April 2016) - Zampagni, Francesca
ABSTRACT: The article focuses on European Consulates as key institutions in the filtering of prospective travelers to the Schengen area. Through qualitative research at the Italian Consulate in Dakar, the article examines the administrative practices surrounding Schengen visas. The article retraces the path travelers have to face to travel with proper documents toward the Schengen area, identifying and analyzing the role of consular bureaucracy in the implementation of the common visa policy at the local level. It will be ascertained whether the notion of street-level bureaucrats can be applied to Consular officials in their daily routine as well as investigating practices of discretion in the decision-making process of visa issuance.